Neurooncology: 2025 update - Mittelbronn, Michel (Free Neuropathology, 2025)
This collection of studies highlights groundbreaking advancements in brain tumor research, particularly primary CNS tumors and brain metastasis. One major focus is the tumor microenvironment, where alterations in cerebral microcirculation and hypoxic-ischemic conditions have been shown to influence metastatic progression. In glioblastoma, recurrent tumors exhibit distinct DNA methylation profiles, and global DNA methylation has emerged as an independent diagnostic marker for IDH-wildtype glioblastoma. A whole-tumor perspective further emphasizes the extensive intratumoral heterogeneity driving glioblastoma evolution. The immune landscape of glioblastoma is another key area of research. Cranioencephalic functional lymphoid units have been implicated in tumor progression, while time-dependent single-cell phenotyping offers novel insights into immune cell dynamics within glioblastoma. Additionally, histone serotonylation has been identified as a critical epigenetic regulator in ependymoma tumorigenesis. Diagnostic and prognostic innovations are paving the way for improved patient care. Histomorphological features provide enhanced prognosis prediction for glioblastoma patients. Confocal laser microscopy enables real-time intraoperative histopathological diagnostics, and sequencing of cerebrospinal fluid-derived cell-free DNA presents a promising non-invasive diagnostic approach. Together, these top studies of 2024 underscore the complexity of brain tumor biology and the integration of epigenetics, immune interactions, and advanced diagnostics into clinical practice. These insights mark significant progress toward personalized treatment strategies and improved outcomes in neurooncology.